Requerimentos ambientais para germinação de sementes de Amaranthus hybridus L. resistente e suscetível a herbicidas - Tronquini, Sérgio Mateus (2023)
Amaranthus hybridus L. is part of the Amaranthaceae family and in recent years the number of cases of herbicide resistance in Brazilian crops has increased. The main purpose of this research is to characterize the germination and emergence of A. hybridus L. biotypes (resistant and susceptible to herbicides) in response to environmental requirements. The project was separated in to two studies, the first was to characterize the environmental factors that interfere with the germination of the species and the second was the influence of different amounts of straw on germination and emergence, as well as the application of pre-emergent herbicides to control the species. For the first study, seven studies were carried out in a completely randomized experimental design with four replications, including the initial characterization of the populations, the influence of photoperiod, the influence of air temperature, the influence of osmotic potential and light quality on the germination of the species. For the second study, three experiments were conducted in a completely randomized design with four replications: the influence of burial depth; the influence of the amount of straw on the emergence of the biotypes; and the influence of the amount of straw on the pre-emergence chemical control of the species. No differences in response were identified between the biotypes tested. A. hybridus L. showed neutral photoblastic seed characteristics, with light being an additive factor, with a temperature range for germination between 20 and 35°C, with the optimum being close to 30°C. Due to the size of the seeds, emergence is affected under water stress of less than -2.0 Bar and soil depth of more than 2.0 cm. The straw influences on emergence in quantities higher than 4 t.ha-1, reduces the population and in interaction with herbicides can be used as a weed-management method. The environmental conditions favorable to the germination of this species are observed in the same months as the soybean crop cycle in the state of Rio Grande do Sul, Brazil, and this is the time to intensify monitoring and management.